KOMPLEKSITAS PENERAPAN PRINSIP RESPONSIBLE TO PROTECT DALAM PENYELESAIAN KASUS PEMBANTAIAN ETNIS ROHINGYA DI MYANMAR (Lex Jurnalica, 2020)
ABSTRACTThis paper aims to explain the complexity of implementing the principle of Responsible to Protect (R2P) in cases of international human rights violations in Myanmar. R2P is a principle in international relations that aims to prevent cases of gross and international human rights violations (genocide, ethnic cleansing, war crimes, and crimes against humans). The use of this principle initially gained a lot of support from countries, but criticism has also arisen since many cases were allegedly constituted as human rights crimes but the Responsible to Protect act did not act appropriately. The concept of intervention that is within the principle of Responsible to Protect is always a consideration and a matter of debate. Although this debate continues and does not seem to stop the commitment of countries to be able to help fellow human beings in other countries still exist in the name of Human Rights. Some of the application of the principle of R2P has been done in Libya, Aceh and several other countries. But in other cases the human rights issues that occur in some countries do not indicate the application of the principle of Responsible to Protect such as the Rohingya case or the Syrian case. Therefore, the use of this principle must be questioned specifically how the issue of human rights can and cannot get the effect of Responsible to Protect in the world. This paper focuses on the influence of human rights in an international context that influences the policies of countries in International Politics to implement the principle of Responsible to Protect.Keywords: Complexity, Human Rights, Myanmar, Responsible to Protect